Oral Rapamycin to Reduce Intimal Hyperplasia After Bare Metal Stent Implantation - A Prospective Randomized Intravascular Ultrasound Study - Cernigliaro, Carmelo; Sansa, Mara; Nardi, Federico; Novelli, Eugenio (IntechOpen, 2012)
None